Pengaruh Work-Life Balance (Keseimbangan Hidup) dan Beban Kerja terhadap Kinerja Pegawai Kantor Kecamatan Samarinda Utara - Arda Siti Amaria; Jubaidi Jubaidi; Rinda Sandayani Karhab (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to empirically analyze the influence of work-life balance and workload on employee performance at the North Samarinda District Office. The background of this study is based on the importance of creating a balance between personal and work and managing a healthy workload to increase the productivity of government apparatus. The research approach used is quantitative with a survey method by distributing questionnaires to 100 employees from the district office and eight villages in the North Samarinda area. Data analysis was carried out using validity and reliability tests, classical assumptions, multiple linear regression, t-test, F-test, and coefficient of determination (R2) with the help of SPSS software version 23. The results of the study indicate that work-life balance has a positive and significant effect on employee performance while workload has a positive but insignificant effect on employee performance. The determination coefficient shows that 27.2% of employee performance variations are run by these variables, the rest is influenced by other factors outside this study. This finding supports the importance of workload policies and management in improving performance in North Samarinda District.